Case-based teacher education preparing for diagnostic judgement. Issue 1 (1st January 2023) - Helleve, Ingrid; Eide, Liv; Ulvik, Marit
ABSTRACT: An integrated part of teaching is to face unexpected situations. Teachers have to make immediate decisions, and these decisions may have a great impact on many people. An important question is how teacher education can prepare students for unexpected situations. The aim of this practitioner research study is to investigate if case-based teaching can contribute to reducing the perceived gap in teacher education. A step-wise model was introduced for the students and data based on the student teachers' experiences was collected through questionnaire and focus-group conversations. The findings show three main arguments for why teacher education should be case-based. First, analysing cases helps students to understand that every situation in practice is unique. Second, cases link to practice and theory, and finally, a case opens for different perspectives depending on how the diagnosis is made.